The Effect of Ursolic Acid from Plantago Lanceolata Leaves on Leukocytes Migration and Chemokines Level - Nanang Fakhrudin; Yuvianti Dwi Franyoto; Eny Dwi Astuti; Arief Nurrochmad; Subagus Wahyuono (Indonesian Journal of Pharmacy, 2019)
Initially considered as a normal body response to injury, inflammation is currently known as a major event contributing to the development of many human disorders. Many drugs and bioactive molecules have been discovered from medicinal plants and the number is still growing by time. Among those medicinal plants used in folk medicines, Plantago lanceolata is used to cure inflammatory-related diseases. In our previous study, we showed that the n-hexane insoluble fraction of P. lanceolata leaves (HIF) demonstrated a potent anti-inflammatory activity by inhibiting leukocytes migration in mice. This study aimed to identify the anti-inflammatory compound from the HIF and to investigate the effect on the chemokines level. P. lanceolata leaves were initially macerated with dichloromethane. The dried extract was partitioned using n-hexane to obtain n-hexane soluble fraction (HSF) and n-hexane insoluble fraction (HIF). Both fractions were evaluated for their anti-inflammatory activities in thioglycollate-induced leukocyte migration. The active fraction (HIF) was subjected to preparative thin-layer chromatography (TLC) to isolate the major compound. The structure of the compound was identified based on NMR, IR, and Mass spectra. Moreover, we investigated the effect of the compound on the level of chemokines responsible for leukocytes migration. The active compound was identified as ursolic acid, based on its spectral data. Ursolic acid at the dose of 30, 60, and 120mg/kg BW inhibited leukocyte migration and reduced chemokines level (IL-8 and MCP-1).